ANALISIS PENDAPATAN, PERTUMBUHAN DAN STRUKTUR EKONOMI NASIONAL - Firdaus Yusuf (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2012)
This paper aims to find out fluctuations in income growth and national economic growth in 2004 - 2008, as one of the important information in the development of national economy, especially to determine the role of development and growth of economic sectors in the national economy. Analysis was performed by diskrptif. While the national income accounts approach based on the Central Bireau of Statistics (BPS) and national economic growth based on the model of growth developed by Roy F.Harrod and Evsey Domar. So that economic growth is simply defined as an increase in total long-term output. The hypothesis of this writing, that the role and growth of industrial sector tended to increase more than other sectors. This has evidenced with the role and growth of every sector of national income as measured by GNP based on constant price and current price.